The Impact of Corporate Social Responsibility Performance Feedback on Corporate Social Responsibility Performance - Lee, Jae-Eun; Yang, Young Soo (Frontiers in Psychology, 2022)
This study empirically analyzes how CSR performance feedback impacts CSR performance, focusing on the performance feedback perspective of behavioral theory of the firm (BTOF). By performing GLS regression analysis based on Korean company data from 2012 to 2019, we presented evidence that positive social and historical performance feedback had a positive effect on CSR performance. Our results provide evidence that firms with higher social and historical CSR performance than CSR aspiration may have higher CSR performance than those that do not.